Galaxy And Mass Assembly (GAMA): the galaxy luminosity function within the cosmic web. Issue 4 (13th March 2015) - Eardley, E.; Peacock, J. A.; McNaught-Roberts, T.; Heymans, C.; Norberg, P.; Alpaslan, M.; Baldry, I.; Bland-Hawthorn, J.; Brough, S.; Cluver, M. E.; Driver, S. P.; Farrow, D. J.; et al.
Abstract : We investigate the dependence of the galaxy luminosity function on geometric environment within the Galaxy And Mass Assembly (GAMA) survey. The tidal tensor prescription, based on the Hessian of the pseudo-gravitational potential, is used to classify the cosmic web and define the geometric environments: for a given smoothing scale, we classify every position of the surveyed region, 0.04 <  z  < 0.26, as either a void, a sheet, a filament or a knot. We consider how to choose appropriate thresholds in the eigenvalues of the Hessian in order to partition the galaxies approximately evenly between environments. We find a significant variation in the luminosity function of galaxies between different geometric environments; the normalization, characterized by ϕ* in a Schechter function fit, increases by an order of magnitude from voids to knots. The turnover magnitude, characterized by M *, brightens by approximately 0.5 mag from voids to knots. However, we show that the observed modulation can be entirely attributed to the indirect local-density dependence. We therefore find no evidence of a direct influence of the cosmic web on the galaxy luminosity function.